Protocolo para la evaluación de la calidad higiénica de la leche cruda de cabra comercializada en Bogotá (2021)
The following work presents a proposed protocol for the evaluation of the hygienic quality of raw goat milk, designed for its potential application in the city of Bogotá, Colombia. Field observations on the raw goat milk trade in the 20 de Julio neighborhood of Bogotá and the Los Rosales municipality in Cundinamarca, in 2020, together with qualitative research based on the collection and consultation of primary and secondary sources, motivated the preparation of the following protocol proposal. Additionally, it is expected to contribute to the development of public health policies (so far nonexistent in the country) that regulate the commercialization and consumption of raw goat milk in the city.